Validation of a population coronary disease predictive system: the CASSANDRA model. Issue 11 (11th March 2014) - Grau, Maria; Subirana, Isaac; Vila, Joan; Elosua, Roberto; Ramos, Rafel; Sala, Joan; Dégano, Irene R; Tresserras, Ricard; Bielsa, Oscar; Marrugat, Jaume
Abstract : Background: The use of validated multivariate cardiovascular predictive models in a population setting is of interest for public health policy makers. We aimed to validate the estimations of the CASSANDRA model (coronary heart disease (CHD) incidence and CHD risk distribution), considering the population changes in age, sex and CHD risk factors prevalence in a 10-year period. Methods: We compared the projected CHD incidence estimated with CASSANDRA with that observed in the Girona Heart Registry (REGICOR) for 1995–2004 and 2000–2009 in the population of Girona (Spain) aged 35–74 years. We used official age and sex distributions for this population. Baseline cardiovascular risk factors prevalence and the distribution of cardiovascular risk were obtained from three cross-sectional studies performed in 1995, 2000 and 2005. To validate the future distribution of cardiovascular risk, we tested the yearly CHD risk variance over the study period. Results: No significant differences between the estimated and observed annual CHD incidence per 100 000 men were found in 1995–2004 (CASSANDRA=457.8 and REGICOR=420.3, incidence rate ratio (IRR) (95% CI)=0.92 (0.89 to 0.96)) and in 2000–2009 (441.4 and 409.6, respectively, IRR=0.93 (0.90 to 0.96)). However, overpredictions of 18% and 22%, respectively, were observed in women (198.8 and 160.4, IRR=0.82 (0.77 to 0.86), and 197.1 and 152.8, IRR=0.78 (0.74 to 0.83), respectively). No significant differences were found in the CHD risk variance in the three different cross-sectional studies. Conclusions: The CASSANDRA model produces valid estimates, particularly in men, of the future burden of disease and in the distribution of cardiovascular risk in individuals aged 35–74 years.